SIFAT TERMO-VISCOUS RESIN FENOLIK DENGAN RASIO MOLAR FORMALDEHID TERHADAP FENOL YANG BERBEDA - Juwono, Ariadne Lakshmidevi; Asraf, Ahmedi; Jihad, Bagus Hayatul; Nugraha Thaha, Yudi (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2024)
Phenolic resin is widely used as a matrix in the composite material. Understanding the thermo-viscous properties of the resin is essential because the viscosity is one of the main factors determining the success of the composite material fabrication. In this study, we synthesized the resin with formaldehyde to phenol molar ratio (F/P) of 1.1, 1.2, 1.3, and 1.4 and analyzed their viscosity as a function of temperature from 17℃ to 25℃. It was observed that the plot of the natural logarithm of the viscosity versus the reciprocal of the temperature of the synthesized phenolic resin is linear. Based on the slope of the Arrhenius plot, the Arrhenius energy of activation varies as a function of the F/P value. The resin’s Arrhenius energy of activation with an F/P value of 1.1, 1.2, 1.3, and 1.4 was 88.8 kJ⁄mol, 96.5 kJ⁄mol, 86.1 kJ⁄mol, and 81.4 kJ⁄mol, respectively. Furthermore, the differential scanning calorimetry (DSC) analysis was conducted on all resins. The endothermic reaction due to water evaporation was found to be dominated at a temperature of around 100℃, and the curing reaction peak of all resins took place at 150℃.